The contribution of the Erasmus+ Programme to Universidade Portucalense: a case study - Silva, Maria Manuela Magalhães (2021)
A case study on the impact of the student mobility aspect of the Erasmus+ Programme at the Universidade Portucalense Infante D. Henrique, located in Porto, Portugal, is presented. The methodology used in this case study relies on a documental analysis, focusing on the doctrinal framework and European Union documentation, targeting the last seven-year framework of the Erasmus+ Programme (2014 to 2021). A brief historical overview of the program is also presented - from its appearance to the present and future mission -, addressing the highly debated question of the European identity and the impact of The Bologna Process in the current academic context. This case study relies on internally collected data between 2014 and 2021, considering the surveys carried out by the institution. Please note that this regional private University has prepared its operations for mobility policies since 1987 and has records of them since 1995